2021
DOI: 10.1109/jsen.2020.3023854
|View full text |Cite
|
Sign up to set email alerts
|

Towards Acoustic Radiation Free Lamb Wave Resonators for High-Resolution Gravimetric Biosensing

Abstract: A novel Lamb wave resonator with fully suppressed acoustic radiation in water is proposed for high-resolution masssensitive detection of biomolecules. The elimination of acoustic radiation is achieved by slowing down the Lamb wave to a velocity lower than the sound speed in water. This enables high-qualityfactor resonance in water and reduces the sensing frequency noise. High aspect ratio electrodes (HAREs) are used to slow down the Lamb wave. The elastic resonance and large surface area of the HAREs can also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…We chose FEM to evaluate the Q factors and mass sensitivities because the experimental values are usually not reported. The simulation models of HARW-LWR and SH-SAW were previously reported in [8]. The simulated S-FBAR comprises of 2-um aluminum nitride (AlN) sandwiched by two 200-nm aluminum electrodes.…”
Section: Performance Of the Sh-pm Resonatormentioning
confidence: 99%
See 1 more Smart Citation
“…We chose FEM to evaluate the Q factors and mass sensitivities because the experimental values are usually not reported. The simulation models of HARW-LWR and SH-SAW were previously reported in [8]. The simulated S-FBAR comprises of 2-um aluminum nitride (AlN) sandwiched by two 200-nm aluminum electrodes.…”
Section: Performance Of the Sh-pm Resonatormentioning
confidence: 99%
“…Nevertheless, the shear polarization cannot prevent the energy leakage through acoustic radiation. To address this problem, phononic metasurface (PM) is introduced 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…It was, however, reported that one-dimensional surface phononic crystals (SPCs) made of periodic high aspect ratio electrode strips can be used to significantly slow down Rayleigh waves 20 and Lamb waves 21 . In this paper, we exploit this idea for the realization of SPC resonators operating in liquid.…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic wave velocity in all piezoelectric substrates is indeed always higher than the sound velocity in water because of the large elastic constants of solid materials. 19 It was however reported that one-dimensional surface phononic crystals (SPC) made of periodic high aspect ratio electrode strips can be used to significantly slow down Rayleigh wave 20 and Lamb wave 21 . In this paper, we exploit this idea for the realization of SPC resonators operating in liquid.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, single-resonator-based (SRB) Micro-Electro-Mechanical-Systems (MEMS) sensors have been extensively studied for detecting small physical or chemical perturbations, such as pressure [1][2][3][4][5][6][7][8], rotational rate [9][10][11][12][13][14], acceleration [15][16][17], vibration [18][19][20], force [21][22][23], chemical vapor [24][25][26], and biological material [27][28][29][30][31][32][33][34]. Various structures, such as flexural mode resonators (FMR) [28,31,35], surface acoustic wave resonators (SAW) [36], bulk acoustic resonators (BAR) [6,12,[24][25][26]37], lamb wave resonators (LWR) [8,14,38], etc., have been fabricated to enable these SRB sensors to ha...…”
Section: Introductionmentioning
confidence: 99%